2021
DOI: 10.3889/oamjms.2021.7183
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers in Online Learning among Nursing Students during the COVID-19 Pandemic in Indonesia

Abstract: BACKGROUND: In March 2020, nursing schools in Indonesia were forced to abruptly shift from face-to-face learning to fully online learning due to the COVID-19 pandemic. Before the pandemic, fully online learning was still not widely used in Indonesian nursing education. AIM: This study aimed to identify barriers in online learning among Indonesian nursing students during the COVID-19 pandemic. METHODS: This study used a cross-sectional design and involved 530 undergraduate nursing students from five univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
1
12
1
2
Order By: Relevance
“…This result is consistent with the findings of other authors (Mohamed Abd El-Hamed Diab & Fouad Elgahsh, 2020;Olum et al, 2020), who also found that technical equipment and support are important in influencing studentsʼ attitudes towards online teaching. Despite previous claims by some authors that quality of Internet connection also influences studentsʼ attitudes towards online teaching (Achmad et al, 2021;Khagi et al, 2021;Mukasa et al, 2021;Olum et al, 2020), the data collected in this study did not yield such a result. No difference was found between the students in terms of the quality and speed of the Internet connection they had while observing online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is consistent with the findings of other authors (Mohamed Abd El-Hamed Diab & Fouad Elgahsh, 2020;Olum et al, 2020), who also found that technical equipment and support are important in influencing studentsʼ attitudes towards online teaching. Despite previous claims by some authors that quality of Internet connection also influences studentsʼ attitudes towards online teaching (Achmad et al, 2021;Khagi et al, 2021;Mukasa et al, 2021;Olum et al, 2020), the data collected in this study did not yield such a result. No difference was found between the students in terms of the quality and speed of the Internet connection they had while observing online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…Nonavailability of computer, internet connection, and accessories can be a barrier for virtual learning. In addition, the software problems related to audio and video conferencing, unfamiliar technology and lack of skill and training of the faculty may pose additional challenges to virtual teaching and learning ( Achmad et al, 2021 ; Khobragade et al., 2021 ; Rotas, & Cahapay, 2020 ; Shahmoradi et al, 2018 ). As highlighted in literature, most participants in the study faced several challenges and were thus dissatisfied with the quality of virtual classes, technology and internet connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Fitriawan et al / KONTAKT 365 pandemic was also a major source of stress among students. A recent study identified numerous barriers during online learning, ranging from the financial to internet connection and technological issues (Achmad et al, 2021). Moreover, the COVID-19 pandemic has also affected students' economic situation, which has a negative impact on their education and may cause them to discontinue.…”
Section: Kontakt / Journal Of Nursing and Social Sciences Related To ...mentioning
confidence: 99%
“…The Coronavirus Disease-2019 (COVID-19) pandemic, declared by the World Health Organization (WHO) in March 2020, has had unprecedented effects on various aspects of human life. Educational sectors have been seriously impacted by the social distancing and lockdown policies implemented to control SARS-CoV-2 transmission (Achmad et al, 2021). Young students' social brains ensure they have stronger desires for social interaction, making them more sensitive to social isolation when lockdown policies are implemented.…”
Section: Introductionmentioning
confidence: 99%